Pertanggungjawaban Hukum perdata Terhadap Kerugian Korban Penyalahgunaan Artificial Intelligence (AI) dan Deepfake di Indonesia - Juniartha Gladys Naomi Magdalena Gultom (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed various aspects of human life, including education, healthcare, business, and digital communication. However, alongside its numerous benefits, AI has also created new legal challenges, particularly through the misuse of deepfake technology. Deepfake technology enables the creation of highly realistic fake images, videos, and audio recordings that can be exploited for fraud, identity theft, defamation, privacy violations, and other unlawful acts, causing both material and immaterial losses to victims. This study aims to analyze the forms of civil liability arising from the misuse of Artificial Intelligence and deepfake technology in Indonesia, as well as to evaluate the effectiveness of the existing legal framework in providing civil legal protection for victims. This research employs a normative legal research method using statutory and conceptual approaches. The study examines relevant legal provisions, including the Indonesian Civil Code, the Personal Data Protection Law, and the Electronic Information and Transactions Law, supported by recent legal literature and scholarly journals. The findings indicate that the misuse of AI and deepfake technology may constitute an unlawful act under Article 1365 of the Indonesian Civil Code when the elements of an unlawful act, fault, damage, and causation are fulfilled. Victims are therefore entitled to seek compensation for both material and immaterial damages through civil litigation. Nevertheless, the current legal framework has not specifically regulated civil liability concerning Artificial Intelligence, resulting in legal uncertainty regarding the responsibilities of AI developers, digital platform providers, and technology users.